2014
DOI: 10.1038/ncomms4029
|View full text |Cite
|
Sign up to set email alerts
|

slanDCs selectively accumulate in carcinoma-draining lymph nodes and marginate metastatic cells

Abstract: Dendritic cells (DCs) initiate adaptive immune responses to cancer cells by activating naive T lymphocytes. 6-sulfo LacNAc þ DCs (slanDCs) represent a distinct population of circulating and tissue proinflammatory DCs, whose role in cancer immune surveillance is unknown. Herein, by screening a large set of clinical samples, we demonstrate accumulation of slanDCs in metastatic tumour-draining lymph nodes (M-TDLN) from carcinoma patients. Remarkably, slanDCs are absent at the primary carcinoma site, while their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 36 publications
(86 citation statements)
references
References 52 publications
7
73
1
5
Order By: Relevance
“…[19][20][21][22][24][25][26] More recently, Vermi et al demonstrated that slanDCs are numerous in metastatic tumor-draining lymph nodes from cancer patients. 28,29 Following these findings, indicating that slanDCs may play an important role in antitumor immunity, we explored the presence of this distinct human DC subset in RCC tissues. slanDCs were preferentially located on the perimeter of tumor nests in close proximity to tumor cells within most metastatic tumor-draining lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22][24][25][26] More recently, Vermi et al demonstrated that slanDCs are numerous in metastatic tumor-draining lymph nodes from cancer patients. 28,29 Following these findings, indicating that slanDCs may play an important role in antitumor immunity, we explored the presence of this distinct human DC subset in RCC tissues. slanDCs were preferentially located on the perimeter of tumor nests in close proximity to tumor cells within most metastatic tumor-draining lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…113 In this context, we have shown that metastatic tumor-draining lymph nodes from carcinoma patients infiltrated by slanDCs also contain, in some cases, CD66b 1 neutrophils within an immunosuppressed like microenvironment. 114 A very recent observation in a head and neck cancer model suggests that neutrophils, previously exposed to tumor-conditioned medium, induce an invasive, NK-resistant, and highly metastatic tumor cell phenotype (S. Brandau, unpublished data, 2014). Another mechanism proposed to explain protumor activities by human and mouse tumor-associated neutrophils consists in their ability to recruit regulatory T cells (Tregs) to the tumor sites, via CCL17 release.…”
Section: Neutrophils In Cancermentioning
confidence: 99%
“…In order to test the specificity of FDCSP and SRGN in FDC-S diagnosis we stained 87 soft tissue tumors, 5 thymomas, 5 melanomas (Supplementary Table 3), 3 interdigitating dendritic cell sarcomas and 114 carcinomas [24]. FDCSP was expressed by two soft tissue tumors, one sinonasal haemangiopericytoma (SNHP-1) and one synovial sarcoma (SS-2); SRGN was negative in all (Supplementary Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…In order to further confirm their specificity, FDCSP and SRGN were additionally applied on TMAs including 114 carcinomas of different origin, previously described [24], and on whole tissue sections of 28 additional control cases (control group #2, Supplementary Table 3). Antibodies applied are detailed in Supplementary Table 5.…”
Section: Methodsmentioning
confidence: 99%